2019
DOI: 10.1097/scs.0000000000005704
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Computer-Aided Design/Computer-Aided Manufacturing-Assisted Mandibular Reconstruction With a Fibula Free Flap

Abstract: Background: The recent increase in computer-aided design and computer-aided manufacturing (CAD/CAM)-assisted surgery has warranted a thorough evaluation of the accuracy of virtual plan execution. Mandibular reconstructions with a fibula free flap were evaluated by comparing the fibular segments postoperatively with the virtual surgical plans. Methods: This study included computed tomography data for 20 patients (11 males; mean age 61.3 years, range 47–7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 30 publications
0
23
0
Order By: Relevance
“…Another essential aspect raised by Numajiri et al is that this form of costeffective planning is done in the surgeon's time and is not outsourced to the osteosynthesis manufacturers and their clinical engineers as is usually the case (28). Geusens et al reported that they have employed a full-time clinical engineer, which could be another solution to the altruistic behavior of interested and motivated surgeons (21). According to Tang et al, the economic benefits and limitations associated with the application of virtual surgical planning must be weighed against patient outcomes (4).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another essential aspect raised by Numajiri et al is that this form of costeffective planning is done in the surgeon's time and is not outsourced to the osteosynthesis manufacturers and their clinical engineers as is usually the case (28). Geusens et al reported that they have employed a full-time clinical engineer, which could be another solution to the altruistic behavior of interested and motivated surgeons (21). According to Tang et al, the economic benefits and limitations associated with the application of virtual surgical planning must be weighed against patient outcomes (4).…”
Section: Discussionmentioning
confidence: 99%
“…The reason is again the heterogeneity of parameters. The majority of studies compared the preoperative virtual plan to the postoperative situation by measuring the fibula segment lengths (21,(29)(30)(31), point-to-point distances and angles (3,13,14), intercondylar distance (32), or intercoronoid distance (21) or by comparing interfragmentary gap distances (33). Numajiri et al analyzed an algorithm for the production of low-cost cutting guides designed and printed inhouse (28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using three‐dimensional (3D) printed reposition guide and metal bone plate for mandible reconstruction is getting more popular (Ciocca et al, 2012). Virtual planning combined improved 3D printing technology has proved to be time saving and increase the accuracy (Geusens et al, 2019). However, the cost of virtual planning and 3D printing is high, even not approved by the authorities yet in some countries, resin cutting guide may be an alternative way to improve the outline of the reconstructed mandible (Nuri et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…54 In addition to the apparent benefits of detailed 3D preoperative surgical planning, higher surgical precision and perioperative time saving is observed. [55][56][57][58] When CAD/CAM is used to produce patient-specific mandibular plates, the precision of the reconstruction is maximized. 59,60 One of the biggest advantages of CAD/CAMaided bony reconstruction is the reduction in flap ischemia time because of the ability to perform osteotomies "in situ" while the pedicle is still intact.…”
Section: Cad/cam Planningmentioning
confidence: 99%